Linking the bacterial community in pea aphids with host-plant use and natural enemy resistance - Ferrari, J; Darby, A; Daniell, T; Godfray, C; Douglas, A (2004)
1. Pea aphids, Acyrthosiphon pisum, harbour a range of facultative accessory bacteria (secondary symbionts), including those informally known as PASS (R-type), PAR, PABS (T-type), and PAUS (U-type). 2. To explore the relationship between possession of these bacteria and ecologically important traits of A. pisum, correlations between the accessory bacteria found in 47 parthenogenetic clones of A. pisum and the host plant on which each clone was collected and its susceptibility to natural enemies were surveyed. 3. The bacterial complement varied with plant of collection. PAUS(U) was present in all of 12 clones affiliated to Trifolium but was otherwise rare, while PABS(T) and PASS(R) occurred at significantly higher frequency in clones from Lotus and Vicia, respectively, than clones from other plants. 4. Possession of PABS(T) was associated strongly with resistance to the parasitoid Aphidius eadyi and weakly with resistance to Aphidius ervi. Aphids carrying PAUS(U) were more resistant to the fungal pathogen Pandora (Erynia) neoaphidis, although this correlation was complicated by a strong association with host-plant use.